Small molecule targeting the Rac1‐NOX2 interaction prevents collagen‐related peptide and thrombin‐induced reactive oxygen species generation and platelet activation. (13th August 2018) - Akbar, H.; Duan, X.; Piatt, R.; Saleem, S.; Davis, A. K.; Tandon, N. N.; Bergmeier, W.; Zheng, Y.
Abstract : Essentials Reactive oxygen species (ROS) generation by NOX2 plays a critical role in platelet activation. Rac1 regulation of NOX2 is important for ROS generation. Small molecule inhibitor of the Rac1‐p67 phox interaction prevents platelet activation. Pharmacologic targeting of Rac1‐NOX2 axis can be a viable approach for antithrombotic therapy. Summary: Background: Platelets from patients with X‐linked chronic granulomatous disease or mice deficient in nicotinamide adenine dinucleotide (phosphate) (NAD(P)H) oxidase isoform NOX2 exhibit diminished reactive oxygen species (ROS) generation and platelet activation. Binding of Rac1 GTPase to p67 phox plays a critical role in NOX2 activation by facilitating the assembly of the NOX2 enzyme complex. Objective: We tested the hypothesis that Phox‐I, a rationally designed small molecule inhibitor of Rac–p67 phox interaction, may serve as an antithrombosis agent by suppressing ROS production and platelet activation. Results: Collagen‐related peptide (CRP) induced ROS generation in a time‐dependent manner. Platelets from Rac1 −/− mice or human platelets treated with NSC23766, a specific Rac inhibitor, produced significantly less ROS in response to CRP. Treatment of platelets with Phox‐I inhibited diverse CRP‐induced responses, including: (i) ROS generation; (ii) release of P‐selectin; (iii) secretion of ATP; (iv) platelet aggregation; and (v) phosphorylation of Akt. Similarly, incubation of platelets with Phox‐I inhibited thrombin‐induced: (i) secretion of ATP; (ii) platelet aggregation; (iii) rise in cytosolic calcium; and (iv) phosphorylation of Akt. In mouse models, intraperitoneal administration of Phox‐I inhibited: (i) collagen‐induced platelet aggregation without affecting the tail bleeding time and (ii) in vivo platelet adhesion/accumulation at the laser injury sites on the saphenous vein without affecting the time for complete cessation of blood loss. Conclusions: Small molecule targeting of the Rac1–p67 phox interaction may present an antithrombosis regimen by preventing GPVI‐ and non‐GPVI‐mediated NOX2 activation, ROS generation and platelet function without affecting the bleeding time.